Risk Indicators for Periodontal Disease in a Remote Canadian Community-a Dental Practice-based Study - Mandy Sbaraglia, DDS; Robert S. Turnbull, MScD; David Locker, PhD (Blackwell Synergy, 2002)
The purpose of this cross-sectional study was to identify risk markers and risk indicators for periodontal attachment loss in a remote Canadian community. Of special interest was the association between smoking and periodontal disease experience